2021
DOI: 10.1101/2021.01.14.426705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation rates and selection on synonymous mutations in SARS-CoV-2

Abstract: The COVID-19 pandemic has seen an unprecedented response from the sequencing community. Leveraging the sequence data from more than 140,000 SARS-CoV-2 genomes, we study mutation rates and selective pressures affecting the virus. Understanding the processes and effects of mutation and selection has profound implications for the study of viral evolution, for vaccine design, and for the tracking of viral spread. We highlight and address some common genome sequence analysis pitfalls that can lead to inaccurate inf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 64 publications
6
87
0
Order By: Relevance
“…Consistent with previous observations 9,16 , a large fraction of the 1,552 homoplasies we detect (60%) derive from C→T changes likely caused by host anti-viral RNA editing machinery 14,15,17 (Supplementary Table S2, Supplementary Figure S2). We detect a significant genome-wide excess of synonymous recurrent mutations compared to non-synonymous changes (Wilcoxon p <1×10 −6 ), a trend largely driven by patterns over the largest open reading frame: ORF1ab (Supplementary Figure S3).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous observations 9,16 , a large fraction of the 1,552 homoplasies we detect (60%) derive from C→T changes likely caused by host anti-viral RNA editing machinery 14,15,17 (Supplementary Table S2, Supplementary Figure S2). We detect a significant genome-wide excess of synonymous recurrent mutations compared to non-synonymous changes (Wilcoxon p <1×10 −6 ), a trend largely driven by patterns over the largest open reading frame: ORF1ab (Supplementary Figure S3).…”
Section: Resultssupporting
confidence: 92%
“…The oxoguanine bases formed are copied as adenine, creating G->T transversions. As ROSs may also target single-stranded RNA, the production of ROSs on viral infections [36] may potentially account for its previously described over-representation of G->U tranversions in SARS-CoV-2 sequences [15][16][17]. We found that higher frequencies of G->U compared to reverse (U->G) or complement (C->A) mutations were more widely found in coronaviruses but broadly absent in the other RNA viruses analysed in the study (S1 Fig) . The presence of ROS is not clearly associated with damage to other bases, such as modifications of cytidines that would template the observed excess of C->U transitions.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…For example, APOBEC3G editing of the single stranded DNA generated by reverse transcription of retroviruses generates a damaged proviral copy unable to direct further retroviral replication [29,30,40]. There has been extensive discussion over whether the observed overrepresentation of C->U transitions in SARS-CoV-2 is driven by one or more of the APOBEC proteins [12][13][14][15][16][17][18]. The current study shows a similar over-representation of C->U changes in the subset of RNA viruses that possessed structured genomes, including other coronaviruses; these finding would therefore predict a strikingly wider breadth of the antiviral activity of this pathway than is currently recognised.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans there are seven A3 enzymes, APOBEC3A-APOBEC3H (A3A-A3H, excluding A3E), which have diverged and expanded from a single enzyme to provide protection against a range of exogenous retroviruses, DNA-based parasites, and endogenous retroelements [1,3,4]. However, misregulation of several A3 family members, in particular the mutagenic actions of A3A, A3B, and A3G, are exploited by viruses (including SARS-CoV-2) [5][6][7] and cancer cells to enhance their rate of evolution, leading to detrimental outcomes by their escaping adaptive immune responses and becoming drug resistant [8][9][10][11][12][13][14]. The A3 members exist as either single-domain enzymes (A3A, A3C, and A3H) or double-domain enzymes (A3B, A3G, A3D, and A3F) made up of two tandem homologous domains with a short flexible linker [15][16][17].…”
Section: Introductionmentioning
confidence: 99%